The relationship between microevolution and macroevolution, and the structure of the extended synthesis - Folguera, Guillermo (2012)
In this article we will focus on the relationship between microevolution and macroevolution. Our main purpose is to argue that, since the consolidation of the evolutionary synthesis up to now, macroevolution has been always conceived as dependent on microevolution. Such dependence was very clear in the synthesis, but seems to have been left aside by later authors. Nevertheless, we will show that the criticisms to the synthesis, broken forth since the decade of the 1970s, did not modify that general trend: the new perspectives reproduced the dependence of macroevolution on microevolution by means of strategies different than those appealed to by the traditional synthesis.